The Drosophila DmGluRA is required for social interaction and memory - Brian P. Schoenfeld; Brian P. Schoenfeld; Richard J. Choi; Richard J. Choi; Catherine H. Choi; Catherine H. Choi; Catherine H. Choi; Catherine H. Choi; Allison M. Terlizzi; Paul eHinchey; Maria eKollaros; Neal J. Ferrick; et al. (Frontiers Media S.A., 2013)
Metabotropic glutamate receptors (mGluRs) have well established roles in cognition andsocial behavior in mammals. Whether or not these roles have been conserved throughoutevolution from invertebrate species is less clear. Mammals have 8 mGluRs whereasDrosophila have a single DmGluRA, which has both Gi and Gq coupled signalingactivity. We have utilized Drosophila to examine the role of DmGluRA in social behaviorand various phases of memory. We have found that flies that are homozygous orheterozygous for loss of function mutations of DmGluRA have impaired social behaviorin male Drosophila. Futhermore, flies that are homozygous or heterozygous for loss offunction mutations of DmGluRA have impaired learning during training, immediate recallmemory, short-term memory and long-term memory as young adults. This workdemonstrates a role for metabotropic glutamate receptor activity in both social behaviorand memory in Drosophila.